2006
DOI: 10.1080/13538320600685222
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Post‐accreditation Scenario in the North Eastern Region of India: a meta‐evaluation of the National Assessment and Accreditation Council processes and procedures

Abstract: The Indian higher education system is one of the largest of its kind in the world. In spite of several built-in quality controls, such as the University Grants Commission's guidelines and the affiliating functions of the university, a deterioration in the quality of higher education was a serious concern for all stakeholders. In 1994 India established the National Assessment and Accreditation Council (NAAC) to ensure and enhance the quality of Indian higher education and also to play an international role as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Institutions introduced changes beyond the mandate of their affiliating systems, including support for R&D by faculty, reduction of faculty workload, and better student support and learning resources (Stella, 2015). Another study by Pillai and Srinivas (2006) in the context of institutions in India's north-east (100 institution heads interviewed) revealed that NAAC had a positive image among the academic community. There was an overall positive impression about the constitution of and interactions with the peer-review team, performance of evaluators, and institutional interface with NAAC.…”
Section: Duration Of Accreditationmentioning
confidence: 99%
See 1 more Smart Citation
“…Institutions introduced changes beyond the mandate of their affiliating systems, including support for R&D by faculty, reduction of faculty workload, and better student support and learning resources (Stella, 2015). Another study by Pillai and Srinivas (2006) in the context of institutions in India's north-east (100 institution heads interviewed) revealed that NAAC had a positive image among the academic community. There was an overall positive impression about the constitution of and interactions with the peer-review team, performance of evaluators, and institutional interface with NAAC.…”
Section: Duration Of Accreditationmentioning
confidence: 99%
“…There was an overall positive impression about the constitution of and interactions with the peer-review team, performance of evaluators, and institutional interface with NAAC. However, there were concerns regarding inter-team variance and geographical advantages enjoyed by urban colleges (Pillai & Srinivas, 2006).…”
Section: Duration Of Accreditationmentioning
confidence: 99%
“…While there is good infrastructure and academic programs, there are problems in other areas and poor performance in research [40]. However, various quality control methods have already been implemented, such as the university affiliation functions or the guidelines of the university grants commission [41]. The National Assessment and Accreditation Council (NAAC) was established in 1994 to ensure and improve quality in higher education and to secure a role at the international level as a quality assurance agency.…”
Section: In Francementioning
confidence: 99%
“…However, continuous feedback from the beneficiaries of education determines the effectiveness of the council. The literature found, in the last 10 years of its reality, that NAAC has earned a lot of generosity and admiration from the learned community (Pillai & Srinivas, 2006). Internal IQAC has established much strategy to consider the quality of the educators in higher education institution.…”
Section: Review Of Related Literaturementioning
confidence: 99%